Answer:
There is strong evidence that less than 87% of the orders are delivered in less than 10 minutes.
Decision rule: Reject the null hypothesis if (P-value < level of significance)
Test statistic z=-2.70
Decision: Reject the null hypothesis (0.003<0.010)
Step-by-step explanation:
In this question we have to test an hypothesis.
The null and alternative hypothesis are:
![H_0: \pi\geq0.87\\\\H_a:\pi](https://tex.z-dn.net/?f=H_0%3A%20%5Cpi%5Cgeq0.87%5C%5C%5C%5CH_a%3A%5Cpi%3C0.87)
The significance level is assumed to be 0.01.
The sample of size n=80 gives a proportion of p=61/80=0.7625.
The standard deviation is:
![\sigma=\sqrt{\frac{\pi(1-\pi)}{N} }=\sqrt{\frac{0.87*0.13}{80} }=0.0376](https://tex.z-dn.net/?f=%5Csigma%3D%5Csqrt%7B%5Cfrac%7B%5Cpi%281-%5Cpi%29%7D%7BN%7D%20%7D%3D%5Csqrt%7B%5Cfrac%7B0.87%2A0.13%7D%7B80%7D%20%7D%3D0.0376)
The statistic z is then
![z=\frac{p-\pi+0.5/N}{\sigma}=\frac{0.7625-0.87+0.5/80}{0.0376} } =\frac{-10125}{0.0376} =-2.70](https://tex.z-dn.net/?f=z%3D%5Cfrac%7Bp-%5Cpi%2B0.5%2FN%7D%7B%5Csigma%7D%3D%5Cfrac%7B0.7625-0.87%2B0.5%2F80%7D%7B0.0376%7D%20%7D%20%3D%5Cfrac%7B-10125%7D%7B0.0376%7D%20%3D-2.70)
The P-value is
![P(z](https://tex.z-dn.net/?f=P%28z%3C-2.70%29%3D0.00347)
The P-value (0.003) is smaller than the significance level (0.010), so the effect is significant. The null hypothesis is rejected.
There is strong evidence that less than 87% of the orders are delivered in less than 10 minutes.
Decision rule: Reject the null hypothesis if (P-value < level of significance)
Test statistic z=-2.70
Decision: Reject the null hypothesis (0.003<0.010)
6x + 7(1-x) = -4(x-4)
6x + 7 - 7x = -4x + 16
-x + 7 = -4x + 16
-x + 4x = 16 - 7
3x = 9
x =9/3
x = 3
Answer:
Tn = 2Tn-1 - Tn-2
Step-by-step explanation:
Before we can generate the recursive sequence, we need to find the nth term of the given sequence.
nth term of an AP is given as:
Tn = a+(n-1)d
If a17 = -40
T17 = a+(17-1)d = -40
a+16d = -40 ...(1)
If a28 = -73
T28 = a+(28-1)d = -73
a+27d = -73 ...(2)
Solving both equations simultaneously using elimination method.
Subtracting 1 from 2 we have:
27d - 16d = -73-(-40)
11d = -73+40
11d = -33
d = -3
Substituting d = -3 into 1
a+16(-3) = -40
a - 48 = -40
a = -40+48
a = 8
Given a = 8, d = -3, the nth term of the sequence will be
Tn = 8+(n-1) (-3)
Tn = 8+(-3n+3)
Tn = 8-3n+3
Tn = 11-3n
Given Tn = 11-3n and d = -3
Tn-1 = Tn - d... (3)
Tn-1 = 11-3n +3
Tn-1 = 14-3n
Tn-2 = Tn-2d...(4)
Tn-2 = 11-3n-2(-3)
Tn-2 = 11-3n+6
Tn-2 = 17-3n
From 3, d = Tn - Tn-1
From 4, d = (Tn - Tn-2)/2
Equating both common difference
(Tn - Tn-2)/2 = Tn - Tn-1
Tn - Tn-2 = 2(Tn - Tn-1)
Tn - Tn-2 = 2Tn-2Tn-1
2Tn-Tn = 2Tn-1 - Tn-2
Tn = 2Tn-1 - Tn-2
The recursive formula will be
Tn = 2Tn-1 - Tn-2
2. Dividing exponential expression with the same base is what the left hand fractional expression is. Z^8/Z^?=z^6. Since all the bases are the same. To get the exponential power 6 on the right we subtract the denominator’s (bottom part of the fraction) exponential power (on the left) from the numerator’s (top part) exponential power.
Then, 8 - ? = 6? 2 is the only number to make the left equal the right side. This, z^8/z^2=z^6
15?im not sure...but I think thats right